ANTESEDEN PENERIMAAN TEKNOLOGI INFORMASI DALAM PROFESI AUDIT INTERNAL DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (Studi Empiris pada Bank Perkreditan Rakyat di Jawa Tengah) - Nugraha, Arya; Laksito, Herry (Diponegoro Journal of Accounting, 2014)
This research is purposed to analyze and find empirical study the effect of organizational factor, social factor, individual factor toward perceived usefulness and perceived ease of use, the effect of perceived usefulness and perceived ease of use toward attitude toward using and behavioral intention to use, the effect of behavioral intention to use toward system usage.Population in this research are all the internal auditors that worked at public credit banking. Sample of this research are internal auditors that worked at public credit banking company in Central Java and willing to complete the questionnaires also minimal have worked 1 years. The analysis data used is PLS program.Based on the result and discussion, the conclusion are: (1) Organizational factor did not affect perceived usefulness. (2) Organizational factor positively affect perceived ease of use. (3) Social factors did not affect perceived usefulness. (4) Social factors positively affect perceived ease of use.(5) Individual factors positively affect perceived usefulness. (6) Individual factors positively affect perceived ease of use. (7) Perceived ease of use positively affect perceived usefulness. (8) Perceived usefulness positively affect attitude toward using. (9)Perceived ease of use positively affect attitude toward using. (10)Attitude toward using positively affect behavioral intention to use.(11) Behavioral intention to use did not affect system usage. (12)Perceived usefulness positively affect system usage.